What Students Say About Gender Violence Within Universities: Rising Voices From the Communicative Methodology of Research. (September 2014) - Vidu, Ana; Schubert, Tinka; Muñoz, Beatriz; Duque, Elena
Gender violence in Spanish universities remains a taboo that is in the process of transformation. The first research on this issue was conducted between 2005 and 2008. The main objective was to "break the silence" about violence against women in Spanish academia. To achieve this aim, data collection was conducted through mixed communicative methods. For the interviewees, the context created by this research made it possible for the first time to establish a space to speak openly about this problem, in contrast to the existing context in which aggressors have remained unpunished. The inclusion of students' voices together with those of administrative staff and professors allowed for the identification of situations of gender violence. This research has had a significant impact on Spanish universities' policies. Despite some institutional barriers that make the implementation of structural changes more difficult, many offices for equality and protocols against gender violence have been created.